A Study on the Strategies of Health Communication of Taijiquan in the Post-Pandemic Era - Li, Lujia; Lu, Fulai; Zhang, Yang; Cui, Meize; Huang, Yuerong (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details